Late renal artery stent fracture with pseudoaneurysm after fenestrated endovascular abdominal aortic aneurysm repair - Shanil M. Yapa, MSc, MBBS; Kishore Sieunarine, FRACS, FRCSE, DDU (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
We report the case of an 81-year-old man incidentally found to have a complete transverse stent fracture of a left renal artery covered stent associated with a pseudoaneurysm while being investigated with digital subtraction angiography for an arterial cause of a nonhealing ulcer on his right great toe. He had a fenestrated endovascular abdominal aortic aneurysm repair 11 years ago with covered stenting of both renal arteries. Although he was asymptomatic, a second left renal artery covered stent was successfully placed across the fractured stent to eliminate the risk of rupture. Follow-up imaging showed patent stent and exclusion of the aneurysm. This case highlights another complication of fenestrated endovascular aneurysm repair that needs to be ruled out on surveillance imaging. Keywords: FEVAR, Fenestrated, Aneurysm, Renal stent, Complication